Synergistic effects of wheat straw powder and persulfate/Fe(II) on enhancing sludge dewaterability. (January 2019) - Guo, Shaodong; Liang, Heng; Bai, Langming; Qu, Fangshu; Ding, An; Ji, Bin; Wang, Xun; Li, Guibai
Abstract: The effects of wheat straw powder (WSP) used as physical conditioner on sludge dewatering was investigated under sodium persulfate (SPS)/Fe(II) oxidation. Sludge dewatering performance in terms of capillary suction time (CST), specific resistance to filtration (SRF) and moisture content (MC) was enhanced with increasing WSP and SPS dosages. The results showed presence of synergistic effect in WSP and SPS conditioning system, with sludge CST and SRF reduced by 43.9% and 65.6%, respectively, after dosing 0.75 g/g DS (dry solid) WSP, 120 mg/g DS SPS and 33 mg/g DS Fe(II), indicating that sludge dewatering became more easily. Correspondingly, bound water was released and decreased from 5.75 g/g DS to 1.5 g/g DS and deep dewatered sludge MC reached to 58.2% under 2 MPa pressure. Mechanically, tightly bound extracellular polymeric substances (TB-EPS) with larger molecular weights were oxidized and degraded into loosely bound-EPS (LB-EPS) and soluble organic matter with smaller molecular weights by SPS/Fe(II). Additionally, the organic matters released from or still in WSP was also oxidized resulting in more channels and less fine particles. Graphical abstract: Sludge was disintegrated by activated Na2 O2 S8 with releasing bound water and wheat straw powder could provide channels for dewatering. Highlights: Wheat straw powder was used as skeleton builder to condition sludge. Sodium persulfate oxidized large molecular substance and release bound water. Wheat straw powder and persulfate synergistically reduced SRF by 77.9%. Wheat straw powder and persulfate reduced sludge cake moisture content by 40.2%.